DEVELOPING STUDENTS’ PRAGMATIC COMPETENCE THROUGH THE “SITUATION–COMMUNICATION–REFLECTION” MODEL - Rustamova Feruzabonu Ilkhomovna (International Journal of Literature and Language Studies, 2026)
Pragmatic competence has become one of the most essential components of communicative competence in contemporary foreign language education. While grammatical accuracy and vocabulary knowledge remain important, successful communication increasingly depends on learners’ ability to use language appropriately according to context, social relationships, cultural norms, and communicative intentions. Many university students demonstrate sufficient linguistic competence but experience difficulties in selecting suitable expressions, interpreting implicit meanings, maintaining politeness, and responding appropriately in real-life interactions. Therefore, innovative pedagogical approaches are required to bridge the gap between linguistic knowledge and practical communication. The “Situation–Communication–Reflection” model offers an effective framework for developing pragmatic competence by integrating authentic situations, interactive communication, and critical reflection. This model encourages students to engage actively in contextualized language use, analyze communicative outcomes, and develop awareness of sociocultural and pragmatic aspects of language. The present article examines the theoretical foundations of pragmatic competence, explores the structure and pedagogical significance of the “Situation–Communication–Reflection” model, and discusses its role in enhancing students’ communicative effectiveness in higher education environments.